Lesional and non-lesional epilepsies: A blurring genetic boundary. (January 2020) - Guerrini, Renzo; Parrini, Elena; Esposito, Alessandro; Fassio, Anna; Conti, Valerio
Abstract: There has been a traditional conceptual partition between the so-called non-lesional genetic epilepsies and the genetically determined interposed epileptogenic structural abnormalities. In this review, we summarise how growing evidence acquired through neuroimaging and neurobiology modelling is demonstrating that a distinction between lesional and functional (or non-lesional) epileptogenesis is less obvious than previously thought, particularly for epileptogenic neurodevelopmental disorders, but also for most genetically determined epilepsies. Highlights: The distinction between lesional and functional (or non-lesional) epileptogenesis is less progressively fading. The use of diagnostic gene panels for epileptogenic disorders is at risk of narrowing down molecular testing out of target. WES is rapidly replacing diagnostic gene panels in the clinical setting.